Adversity Quotient as a Predictor of Employee Performance at PT X in Surabaya - Vidya Nindhita; Wasis Purwo Wibowo (Journal of Social and Industrial Psychology, 2026)
Employee performance determines how a company will operate. Given the challenges and obstacles faced in the workplace, employee performance will decline if not balanced by appropriate personal competencies and resilience in the face of problems. The ability to cope with difficulties or challenges is essential for individuals to achieve success. Employees with a high Adversity Quotient are expected to be able to face any problems that come their way and continue to turn them into great potential for themselves, and ultimately maintain maximum performance within the company. The purpose of this study is to uncover the role of the Adversity Quotient in employee performance at PT X in Surabaya. This study uses a quantitative research method with a correlational design. The sampling technique used purposive sampling, with the following population criteria: a) employees, both male and female; b) length of service > 1 year. Data analysis employed simple linear regression. The results indicate that AQ has a significant influence on employee performance. One implication of this study is that the company can integrate AQ development into its existing policies.